Effect of mesoporous silica nanoparticles‐based nano‐fragrance on the central nervous system. Issue 11 (4th June 2020) - Lu, Zhiguo; Zhang, Tianlu; Yang, Jun; Wang, Jianze; Shen, Jie; Wang, Xiangyu; Xiao, Zuobing; Niu, Yunwei; Liu, Guiying; Zhang, Xin
Abstract: Fragrances are widely used in our daily lives and can make us feel happy. However, traditional aromatic products release fragrance quickly and have a strong aroma. This not only worsens our scenting experience, but also severely shortens the useful life of fragrance products. In this study, nano‐fragrances based on mesoporous silica nanoparticles with great encapsulation efficiency and slow‐release function were designed and prepared. In addition, this nano‐fragrances are applied to wallpapers. Open field tests showed that this nano‐fragrance had significant stress relief and anti‐depressant effects.